THE ROLE OF PROBLEM-BASED LEARNING MODELS IN GEOGRAPHY LEARNING IN BUILDING STUDENT ECOLITERACY - Intan Paramida Wardyani (Geographica: Science and Education Journal, 2021)
Ecoliteracy can be said to be ecological literacy or environmental literacy where humans have a high level of awareness of the importance of the environment for life. Problem Based Learning model is a learning model by presents real problems that are happening so that the model can be used in geography learning. Geography itself is a science that studies the interaction between humans and their environment, the existence of geography learning can make it easier for teachers to grow ecoliteracy in students. Cognitive knowledge of students increases where they can remember to the ability to solve problems, affective, namely the attitude of students has led to protecting the environment and for their own psychomotor students already have the desire to act such as throwing garbage in its place and doing things related to cleanliness at school . So with these things ecoliteracy in students has begun to grow.